Uji Sertifikasi Manajer Lapangan Pelaksanaan Bangunan Gedung Bagi Calon Wisudawan Prodi Jenjang D4 Sebagai Surat Keterangan Pendamping Ijazah - Tjendani, Hanie Teki; Risma Marleno; Esti Wulandari; Laksono Djoko Nugroho; Shinta Berlinda Wulandari; Aviska Triayaska (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Every construction worker engaged in the construction services field must have a Work Competency Certificate (Sertifikat Kompetensi Kerja Konstruksi/SKK Konstruksi). Every owner and service provider must employ construction workers with an SKK Konstruksi. Construction Service work contracts must include the use of certified construction workers. The SKK-K is a mandatory requirement for working in the construction services sector. This paper will discuss the competency assessment activities conducted by recent D4 graduates to obtain a work competency certificate for the job position of Building Execution Field Manager Level 6. This serves as a graduation requirement and as a Supplementary Diploma Certificate (SKPI; surat keterangan pendamping ijazah). In this assessment, all assessors passed and were declared competent. The students' capabilities are supported by fieldwork practice activities, which are included in the curriculum of their respective study programs. The students have passed the competency assessment, meaning that upon graduation, they already hold both a diploma and a Work Competency Certificate